ANALISIS YURIDIS TERHADAP PEMBERHENTIAN SECARA TIDAK HORMAT DAN PEMBATALAN PEMECATAN NOTARIS STUDI KASUS PUTUSAN PENGADILAN TATA USAHA NEGARA NOMOR : 235/G/2019/PTUN.JKT - Riandy, Novi; Ginting, Budiman; Azwar, Tengku Keizerina Devi (BULETIN KONSTITUSI, 2022)
In the economic and socio-cultural life of today's society, notarial institutions play the most important role in people's lives, this can be seen and felt by people who want to carry out a legal action. For example, it can be seen in terms of the business world which is increasingly broad and growing, such as buying and selling, leasing, accounts payable and so on. Notaries as ordinary people, in carrying out their duties, can make mistakes or violations. A Notary who is proven to have violated the obligations and prohibitions of a Notary as regulated in Articles 16 and 17 of Law Number 2 of 2004 concerning Amendments to Law Number 30 of 2004 concerning the Position of a Notary, can be subject to sanctions in the form of civil sanctions, administrative sanctions, sanctions code of ethics and even criminal sanctions. In conducting this research, normative juridical research is used which has a method that is different from other research. The normative juridical research method is adopted by a system of reviewing a number of archives of related legislation, books, books and other scientific works in the library that can be used as a source of this research. This study shows that the object of the lawsuit in the decision of the State Administrative Court Number: 235/G/2019/JKT in the form of the Decree of the Minister of Law and Human Rights of the Republic of Indonesia Number: AHU.55.AH.02.04 YEAR 2019 concerning Disrespectful Dismissal from the Notary Position on behalf of Muhammad Irsan, S.H., Notary in Tangerang City violated the General Principles of Good Government based on Article 53 paragraph (2) letters a and b of Law Number 9 Year 2004 concerning State Administrative Court. law is certainty and justice, so in the case of dismissal of a notary must consider the elements that occur.